The Study of Certain Types of Natural Fibers Determination of Their Properties by Organoleptic and Laboratory Methods - Rashidov Asamiddin Zayniddinovich (Genius Journals, 2022)
This article discusses the study of certain types of natural fibers, the determination of their properties by organoleptic and laboratory methods - distinctive features in the study of the structure of natural fibers using light and a microscope.
Keywords: Natural fibers; cellulose fibers; cotton; linen